Corrosion of carbon steel under condensing water and monoethylene glycol - Islam, Md. Mayeedul; Pojtanabuntoeng, Kod; Gubner, Rolf (Elsevier, 2018)
© 2018 Elsevier Ltd The influence of monoethylene glycol (MEG) on the condensation process and corrosion behaviour of carbon steel is investigated. The results show that increasing MEG concentrations at the bottom of the line increases MEG co-condensation, reduces condensation rates and, consequently, uniform corrosion rates. However, localised corrosion occurs and pits aggregate within the droplet boundary when MEG co-condenses with water. The corrosion product comprises of FeCO3embedded in a Fe3C matrix. Its thickness in the areas outside the condensed droplet boundary is greater compared to that of the inside. Localised corrosion mechanism of carbon steel under condensing MEG and water is proposed.